Computational scheme for a differential - difference equation with a large delay in convection term - Erla, Srinivas; Kolloju, Phaneendra (Zielona Góra: Uniwersytet Zielonogórski)
A computational scheme for the solution of layer behaviour differential equation involving a large delay in the derivative term is devised using numerical integration. If the delay is greater than the perturbation parameter, the layer structure of the solution is no longer preserved, and the solution oscillates. A numerical method is devised with the support of a specific kind of mesh in order to reduce the error and regulate the layered structure of the solution with a fitting parameter.
Keywords: delay differential equations; layer behavior; large delay; fitting parameter